The usual discourse of sustainable development and its impact on students of economics: a case from Czech higher education context. Issue 5 (11th October 2021) - Buchtele, Roman; Lapka, Miloslav
Abstract : Purpose: In recent decades, the concepts of sustainable development (SD) and sustainability have become a part of the everyday information flow. Is there real impact on students who have potential to become stakeholders and decision-makers? To be able to answer this question, the authors focussed on the following problems: whether the discourse of SD has any impact on students of economics concerning their knowledge of the environmental pillar of SD; and whether it has an impact on their individual value orientation towards the New Ecological Paradigm (NEP). Design/methodology/approach: A group of 120 university students of economics programs from the Czech Republic was chosen for the quantitative research of this study. About a half of them have already encountered environmental education. The questionnaire included topics of environmental pillar of SD and revised NEP scale. Findings: Using correlation analysis, the results show that the discourse of SD does have an impact on the students' knowledge of the environmental pillar of sustainability and it also has an impact on their individual value orientation towards the NEP in general. The knowledge of the environmental pillar of SD is not significantly influenced by the study of a subject which included the topic of SD and its principles. Value orientation towards NEP is not significantly influenced by the study of a subject which, among other things, included the topic of SD and its principles. Research limitations/implications: Findings should be accepted with the knowledge of the limited sample from one country, on the other hand, information flow – usual discourse of SD is global. Social implications: There is positive NEP orientation among the students of economics – young women and men have pro-environmental attitudes. This can be considered as great unused social potential in higher education. Originality/value: This study deals with knowledge of SD, environmental education and value orientation. It is broader concept taking into account the real social environment in terms of usual SD discourse and individual value orientation, not only direct influence of education on knowledge. The study rejected direct impact of the environmental education on knowledge and value orientation in terms of SD discourse among the students of economics. The findings bring several important questions regarding the effective forms of environmental education.